Optimizing safety performance through risk-based modeling in Nigeria’s oil and gas sector - Mgbowaji Zacchaeus; John Ugbebor; Ikechukwu Agbagwa; Ochuko Felix Orikpete (The Journal of Engineering and Exact Sciences)
The Nigerian oil and gas sector is fraught with safety challenges that undermine operational integrity and worker welfare. Addressing these issues requires a nuanced risk-based intervention and modeling approach to improve safety performance. This study investigated the safety challenges in Nigeria's oil and gas sector, focusing on identifying and addressing hazards to enhance operational integrity and worker welfare. A semi-quantitative approach was used to develop a comprehensive hazard checklist, aligned with ISO standards and expert insights. Data on hazard likelihood and severity were gathered through questionnaires distributed among a diverse group of industry experts, workers, and stakeholders. The analysis highlighted key risks like inadequate infrastructure, valve and seal failures, security concerns, and oil spill risks, underscoring the need for targeted interventions to promote a safer working environment and reduce accident risks.